2017
DOI: 10.1007/978-1-4939-7398-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Polyamine Metabolism Responses to Biotic and Abiotic Stress

Abstract: Plants have developed different strategies to cope with the environmental stresses they face during their life cycle. The responses triggered under these conditions are usually characterized by significant modifications in the metabolism of polyamines such as putrescine, spermidine, and spermine. Several works have demonstrated that a fine-tuned regulation of the enzymes involved in the biosynthesis and catabolism of polyamines leads to the increment in the concentration of these compounds. Polyamines exert di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…Polyamines are known to play an important role in osmotic regulations, membrane stability, and the removal of free radicals under abiotic stresses (Liu et al 2007;Romero et al 2018). In accordance with earlier studies, the overexpression of both FvSAMS and FvSAMDC was found to increase the total polyamine levels in response to stress (Roy and Wu 2002;Waie and Rajam 2003;Wi et al 2006Wi et al , 2014Cheng et al 2009;Peremarti et al 2009;Gong et al 2014;Ma et al 2017).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Polyamines are known to play an important role in osmotic regulations, membrane stability, and the removal of free radicals under abiotic stresses (Liu et al 2007;Romero et al 2018). In accordance with earlier studies, the overexpression of both FvSAMS and FvSAMDC was found to increase the total polyamine levels in response to stress (Roy and Wu 2002;Waie and Rajam 2003;Wi et al 2006Wi et al , 2014Cheng et al 2009;Peremarti et al 2009;Gong et al 2014;Ma et al 2017).…”
Section: Discussionsupporting
confidence: 87%
“…High salt levels cause ion toxicity (mainly Na + ), hyperosmotic stress, and secondary stresses (i. e. oxidative damage) (Zhu 2002;Chinnusamy et al 2006). Both ethylene and polyamines (putrescine, spermidine and spermine) play an important regulatory role in the biotic and abiotic stress responses of plants (Müller and Munné-Bosch 2015;Romero et al 2018) and in larger quantities they have a positive effect on the salt tolerance of plants (Jang et al 2012;Peng et al 2014;Shen et al 2014). The antioxidant enzyme activity is growing on the effect of adequate concentration of both ethylene and polyamine, by this way they increase the homeostasis of reactive oxygen species (ROS) and regulate the balance of Na/K, enhancing the adaptation of plants to the salinity environment (Saha et al 2015;Tao et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The major polyamines (PA) in plants are the diamine, putrescine (Put), the triamine, spermidine (Spd) and the tetraamine, spermine (Spm). They function in key developmental and physiological events 52 as well as taking part in plant response to stresses 53 . As for DAP associated with the metabolism of polyamines, the majority are involved in polyamine degradation, and their abundance increased in HOi/WTi.…”
Section: Polyamine and Phytohormone Signaling And Metabolism Dap Assmentioning
confidence: 99%
“…It is now accepted that plant polyamines, including Put, Spd, and Spm, take part in various biological processes, such as morphogenesis, senescence, and fruit development, as well as abiotic and biotic stresses (Handa & Mattoo, 2010;Teh et al, 2014;Minocha, Majumdar, & Minocha, 2014;Ebeed, Hassan, & Aljarani, 2017;Guo et al, 2018;Fortes & Agudelo-Romero 2018;Handa, Fatima, & Mattoo, 2018;Hao et al, 2018;Romero et al, 2018;Zahedi, Hosseini, Karimi, & Ebrahimzadeh, 2019). Since early reports on a role of PAs in fleshy fruits (Cohen, Arad, Heimer, & Mizrahi, 1982;Winer, Vinkler, & Apelbaum, 1984), over the past years, much progress has been made toward understanding PA roles in fruit development and ripening (Kushad et al, 1988;Dibble et al, 1988;Rodriguez et al, 1999;Lester, 2000;Bregoli et al, 2002;de Dios et al, 2006;Parra-Lobato & Gomez, 2011;Koushesh et al, 2012;Kitashiba, Hao, Honda, & Moriguchi, 2005;Jiang et al, 2015;Fortes et al, 2015;Simpson et al, 2017;Guo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%